Organic hosted porosity in the Wufeng-Longmaxi shale: A combined electron microscopy and neutron scattering approach - Delle Piane, C.; Ansari, H.; Rickard, William; Saunders, M.; Mata, J.; Dewhurst, D.N. (2019)
© 2019 European Association of Geoscientists and Engineers, EAGE. All Rights Reserved. The upper Ordovician Wufeng shale and lower Silurian Longmaxi shale are part of the Fuling shale gas play located in the south-eastern part of the Sichuan Basin, southern China, representing the first commercial shale gas production project outside North America. We studied the occurrence of porosity at micro- and nano-scale in samples of contrasting organic richness from the post‐mature part of the Wufeng-Longmaxi gas play. Using a combination of high resolution scanning and transmission electron microscopy and small angle neutron scattering we highlight the impact of different types of organic matter (primary versus migrated) on the development of organic matter (OM)-hosted porosity. The results indicate that the overall porosity in the samples is proportional to the organic richness, although the nanoscale imaging revealed that OM-hosted porosity is preferentially present in the migrated bitumen and not in the primary detrital particles. Distinguishing between primary and migrated OM is therefore important for understanding the creation of an interconnected network of OM during hydrocarbon migration. This may have an important control on the estimation of gas in place and the transport properties of the shale.